THE INFLUENCE OF ORGANIZATIONAL CULTURE, SELF-EFFICACY, AND WORK DISCIPLINE ON TEACHER PERFORMANCE - Simarmata, Meri Anjelina; Hadi, Syamsul; Purnamarini, Tri Ratna (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Teacher performance is the result of real work in terms of quality and quantity achieved. Some literature on improving performance still has inconsistencies such as organizational culture. In several articles it has been proven to have a positive influence, however, other research has not been proven to have an effect on teacher performance. The aim of this research is to analyze organizational culture, self- efficacy, and work discipline on teacher performance. The research methodology involved 55 high school respondents with a sampling technique using a census sample. while data processing uses SPSS version 23. The results of the research show that organizational culture can be concluded that the hypothesis is proven to have an effect on teacher performance, but self-efficacy and work discipline on teacher performance can be concluded that the hypothesis is not proven to have an effect on teacher performance. The results of several literature reviews provide an in-depth understanding of the positive relationship between the influence of organizational culture, self-efficacy and work discipline on teacher performance, and these findings can be used as a reference for future empirical research.